European economic integration and (A)symmetry of macroeconomic fluctuations - Clemens J. M. Kool; Claire Economidou (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2007)
This paper empirically investigates output and consumption asymmetries in the Eurozone and enlarged EU over the period 1992-2007, and their consequences for monetary policy. Our results reveal that the introduction of the euro has little impact on output asymmetry so far; however, it has led to somewhat greater consumption smoothing. The UK, Denmark and Sweden are no less asymmetric than the average Eurozone member state and could probably enter the EMU without significant macroeconomic costs. New EU member states are diverse but display higher output and, in particular, consumption asymmetries. This warrants caution against too quick expansion of the EMU.
Keywords: 330; Integration; Macroeconomic Asymmetries; Welfare Gains; Risk Sharing; Euro